PENGARUH ORIENTASI KEWIRAUSAHAAN DAN AKSES KEUANGAN TERHADAP KINERJA USAHA - Putra, Muchammad Rizki Agung; Nuzula, Nila Firdausi; Mawardi, Muhammad Khalid (Profit: Jurnal Adminsitrasi Bisnis, 2021)
This study attempts to explain the influence of orientation entrepreneurship and financial access on their performance. Business research by analyzing the effectiveness of the KUR program bri given to the offender SME’s in Blitar East Java. With a technique, the sample collection non-probability in random proportionate, with the data was path analysis. The result showed that orientation entrepreneurship positive effect on access to finance, entrepreneurial orientation also has a relationship significantly to the performance of businesses either directly or indirectly financial access addition, financial access to depend on the performance of business.